INVESTING IN OBSOLESCENCE. - Castenhole, W. B. (The Accounting Review, 1928)
Obsolescence is an investment in future and better operations. This article is concerned with obsolescence which occurs only from time to time in any ordinary business. It may be, that the more extensive and often cataclysmic obsolescence, which often presents itself in special industries such as public utilities, may deserve different treatment, under those conditions it may be impossible to make future operations the basis for its absorption. Additional capital may have to be called upon to take care of the situation, that fact however, in itself, would indicate as investment in obsolescence, or in progress. The new capital stands in place of the new equipment and the obsolescence created thereby. In connection with this proposition of obsolescence, as well as with other things, the writer has often wondered whether accepted accounting practices are not being influenced by certain opportunistic factors, of which Federal Income Tax legislation is doubtless one. Unfortunately, many sound principles are often discarded, or denied, when dollars are involved.